Use of anthropomorphic compressed breast phantoms for comparing ultrasound breast imagers - KELLY-FRY, E.; MADSEN, E. L.; FRANK, G. R. (Archives of Acoustics, 1991)
Two anthropomorphic breast phantoms were used to compare state-of the art ultrasound imagers. The phantoms mimic refractive effects at fat to nonfat boundaries, and include simulated and pathological structures like fibroadenomas, cysts, calcifications and malignant tumors. Images of those structures obtained by means of various ultrasound systems are compared and discussed. In conclusion, the authors recommend use anthropomorphic breast phantoms which simulate the acoustic characteristics of normal and pathological breast tissues to test ultrasound mammography systems prior to their routine use on patients.